Towards generic modelling of hospital wards: Reuse and redevelopment of simple models. Issue 2 (2nd April 2020) - Penn, M.L.; Monks, T.; Kazmierska, A.A.; Alkoheji, M.R.A.R.
ABSTRACT: Generic simulation models are designed to enable model reuse. We argue that there are two weaknesses within the generic simulation modelling literature. Firstly, that generic models sacrifice the relative simplicity of a bespoke simulation model for flexibility. Secondly, that generic models are published in conceptual form only. If researchers cannot access computer implementation of models, then there is little incentive or benefit to recode one over coding a simpler bespoke simulation model. We introduce an incremental approach to generic modelling in discrete-event simulation. We develop an archetype setting-specific generic model of a hospital ward. The archetype model is first developed and applied in a rehabilitation ward setting. Then a second team applies the model in a specialised intensive care setting. We report the successes, obstacles and redevelopment needed for reuse of the generic model along with how the results of these studies were used to inform healthcare delivery.